ADOLESCÊNCIA NORMAL?: um estudo acerca do submetimento à função paterna - GOMES, Alyssandra Vieira Costa (2015)
Adolescence is a recent phenomenon that starts to take its social place on the XIX century. Even though it didn’t receive proper theoretical evidence in Psychoanalysis, adolescence makes itself present in Freudian and Lacanian texts. Freud, in his classical work “Three Essays on the Theory of Sexuality”, dedicates one of the essays to the changes that take place in puberty. Adolescence coincides with puberty, so we can notice that this moment is not an easy one and specially not one easy to go through. Changes occur: on the body, on the way of thinking and acting and also in the position one occupied before. The main goal of this paper was to discuss how the submission to the paternal function makes a “normal” adolescence possible, based on the analysis of the movie “Before the World Ends”. As resulting branches of the proposal of the movie analysis, the research tried to identify in its specific objectives the following aspects: theoretical considerations by Sigmund Freud on the Oedipus complex and castration and, by Lacan, on the paternal function. In order to do so, a bibliographic research was performed based on Freud’s indications about the psychoanalytical method, which has as specificity the unconscious overdetermination and, consequently, its inapprehensible character. This paper presents Freudian notions of infantile sexuality, of the Oedipus complex and of the genital phallic organization as well as the subjective implications of these issues to the adolescent. The paper also present contributions by Jacques Lacan, based of Freud’s work, on the paternal metaphor, the three “times” – that is to say the three moments – of the Oedipus complex and how they reflect on a “normal” adolescence. In what concerns the discussion of the movie, the following sequence was privileged when presenting the material: from the scene where Daniel receives the first letter by his biological father – of whom he hadn’t known before – to the moment when he receives an invitation to go and meet him. We highlight how adolescence is permeated by contradictions, difficulties, joys, conquest and losses. Based on the discussion, we indicate that the paternal function is not exclusively referred to the real existence of a father, but on the symbolic marks left by him who, as pointed Lacan, is in the center of the Oedipus question. In the movie, the character Daniel starts to dress himself with photographer’s clothes just like his father. From there, if the father cannot give answers to his questions, it’s through the identification that Daniel will build his own answers. The paternal function makes it possible for the adolescent to go from adolescence to a different time, this one being a subjective time, related to the responsibility to his own desire.